2020
DOI: 10.1186/s12903-020-01219-y
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal status, perceived stress, diabetes mellitus and oral hygiene care on quality of life: a structural equation modelling analysis

Abstract: Background: To determine if periodontal risk assessment (PRA), the number of missing teeth, diabetes mellitus (DM), perceived stress and interproximal cleaning are associated with oral health-related quality of life (OHRQoL), using Andersen's behavioral modelling (ABM). Material and methods: Data derived from 472 adults derived from a representative population of the Study of Periodontal Health in Almada-Seixal (SoPHiAS) was used. Socioeconomic status, perceived stress scale (PSS-10), oral health behaviors and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 72 publications
3
27
1
2
Order By: Relevance
“…The major limitations of the current study include the crosssectional design that precludes causal inferences, the small sample size, and possible effects of unaddressed predictors such as nutritional status, lifestyle-related risk factors, genotype, the possibility of occult infection, level of antenatal care level, physical activity, weight gain, sleep, psychological status, among others (16,(55)(56)(57)(58)(59)(60). To compensate in part, a SEM model was thus designed to construct and model unobserved or latent dimensions and has been previously applied in periodontal research (61)(62)(63)(64)(65). Furthermore, this study design fails to address the possible syndemic nature of the association between periodontal inflammation and systemic state, whereby vulnerable subsets may be affected by both periodontal and other inflammatory conditions (66).…”
Section: Discussionmentioning
confidence: 99%
“…The major limitations of the current study include the crosssectional design that precludes causal inferences, the small sample size, and possible effects of unaddressed predictors such as nutritional status, lifestyle-related risk factors, genotype, the possibility of occult infection, level of antenatal care level, physical activity, weight gain, sleep, psychological status, among others (16,(55)(56)(57)(58)(59)(60). To compensate in part, a SEM model was thus designed to construct and model unobserved or latent dimensions and has been previously applied in periodontal research (61)(62)(63)(64)(65). Furthermore, this study design fails to address the possible syndemic nature of the association between periodontal inflammation and systemic state, whereby vulnerable subsets may be affected by both periodontal and other inflammatory conditions (66).…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is the patients’ inability to report, precisely, the cause of tooth loss. Recent studies in this regional area, but also at a national level, have demonstrated the serious ignorance regarding oral health, its consequences and oral hygiene habits [ 63 , 64 , 65 , 66 , 67 , 68 ]. Thus, it would be very risky to consider self-reported data regarding the cause of tooth loss.…”
Section: Discussionmentioning
confidence: 99%
“…This model accounts for solely clinical measures and with high reliability performance, hence it may be commissioned in large-based studies to predict tooth loss in the short-term. To the public health view, this conceivable information might be crucial to delineate and prepare appropriate measures to target tooth loss and edentulism, both recognized as disturbing public health problems and with devastating consequences for oral health-related quality of life [2,29,30].…”
Section: Discussionmentioning
confidence: 99%